2014
DOI: 10.1136/flgastro-2014-100530
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a new disease severity index: the Inflammatory Bowel Disease Index (IBDEX)

Abstract: Objective To develop, validate and apply a generic clinical severity index applicable to all adult patients with inflammatory bowel disease (IBD). Design A review of the literature and an expert focus group consultation were carried out in order to draw out relevant items from existing literature. The new index was called the IBD Index (IBDEX). Standard psychometric analysis was carried out. The construct validity was assessed against biochemical markers, clinical and endoscopic indices. The new index was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…Considering lower prevalence of traditional CV risk factors in IBD-WCH patients one could argue that WCH in IBD is not associated with higher CV risk and consecutively that high prevalence of WCH could not contribute to the observed higher CV risk in IBD patients. It was reported that WCH is associated with early vascular aging and two meta-analyses confirmed that subjects with WCH, both treated and untreated, have increased cf-PWV compared to the normotensive subjects [27,29,37,53,54] which was in line with our results. It was proposed that observed higher CV risk in WCH partly could be explained with higher PWV, i.e., higher arterial stiffness.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Considering lower prevalence of traditional CV risk factors in IBD-WCH patients one could argue that WCH in IBD is not associated with higher CV risk and consecutively that high prevalence of WCH could not contribute to the observed higher CV risk in IBD patients. It was reported that WCH is associated with early vascular aging and two meta-analyses confirmed that subjects with WCH, both treated and untreated, have increased cf-PWV compared to the normotensive subjects [27,29,37,53,54] which was in line with our results. It was proposed that observed higher CV risk in WCH partly could be explained with higher PWV, i.e., higher arterial stiffness.…”
Section: Discussionsupporting
confidence: 93%
“…It was reported that WCH is associated with early vascular aging and two meta-analyses confirmed that subjects with WCH, both treated and untreated, have increased cf-PWV compared to the normotensive subjects [27,29,37,53,54] which was in line with our results. It was proposed that observed higher CV risk in WCH partly could be explained with higher PWV, i.e., higher arterial stiffness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Disease specific scores after treatment using IBDex severity scoring index, 32 Crohns and Ulcerative Colitis Questionnaire (CUCQ)-32 severity scoring index 33 and Mayo scoring system 34 …”
Section: Methodsmentioning
confidence: 99%
“…To overcome this disconnect between research/regulatory practice and clinical practice, there is need for alternative measures of outcome, and thereafter definitions of response. Part of this process is the development of patient-reported outcomes, but in this edition of Frontline Gastroenterology Alrubaiy and colleagues propose a combination of end points—the IBDex©—from existing indices to complement such assessment 1. A challenge of these composite indices is to make them readily applicable in practice, and the authors propose achieving this with high validity and simplicity of scoring by recording over the last three days.…”
Section: Do We Need Another Inflamatory Bowel Disease (Ibd) Severity mentioning
confidence: 99%